The advantages of using an electrochemical quartz nanobalance to study the electrochemical conversions of solid microparticles - Inzelt, Gyorgy (Array, 2009)
Summary: This paper discusses the importance of and opportunities for applying piezoelectric nanogravimetry in the investigation of immobilized microcrystals on electrodes. The selected experimental results presented shed light on the complex nature of the processes occurring in these systems. The problem of the first cycle or break-in effect is emphasized